New evidence for through-space transmission of substituent effects in benzene derivatives - Segurado, MAP (2015)
Electrostatic interaction energies between dipolar substituents and dipolar or charged reaction sites are re-examined. At short interaction distances and given orientations, the point-dipole approximation is shown to introduce important errors. Exact expressions are derived for correcting current equations for both interaction types, including the Kirkwood-Westheimer equation. The parameter for describing para-meta ratios of substituent inductive or Electra effects in benzene derivatives is modelled in terms of electrostatic interaction energy. Using the new equations it is shown that parameter can take values smaller or greater than unity, approaching a value of 2 at very large distances. Experimental values are calculated using reliable literature data for the ionisation equilibria of substituted phenylethanoic and 3-phenylpropanoic acids in ethanol-water mixtures. Theoretical values for these reactions are obtained taking into account rotational and conformational changes in the corresponding carboxylate anions. From the good agreement between experimental and theoretical values, it is concluded that there is through-space transmission of substituent effects in benzene derivatives.